Effects of the proportion of students with special educational needs on middle school teachers’ well-being - Chen, Yuan (Frontiers in Education, 2024)
This study explores the impact of the proportion of students with special educational needs (SEN) on Chinese middle school teachers' job stress, satisfaction, and exhaustion, amid increasing emphasis on inclusive education. The research hypothesizes that a higher proportion of SEN students may lead to increased job stress, decreased job satisfaction, and heightened job exhaustion. This study utilized data from the China Education Panel Survey, and Structural equation modeling was used for data analysis. The study found a significant negative association between the proportion of SEN students and teacher job satisfaction (β=-0.09, p<0.05). No direct relationship was found between the proportion of SEN students and job stress (β =0.00, p>0.05) and job exhaustion (β =-0.08, p>0.05). However, there was an indirect positive impact of the proportion of SEN students on job exhaustion via job satisfaction (β =0.05, p<0.05). This research provides valuable insights into potential strategies for enhancing job satisfaction and reducing job exhaustion among teachers with a high proportion of SEN students.